Underwater passive manoeuvring target tracking with isogradient sound speed profile - Jun Su; Yaan Li; Wasiq Ali (IET Radar, Sonar & Navigation, 2022)
Abstract Compared with the traditional tracking problem, the underwater 3‐D passive manoeuvring target tracking faces the following challenging problems: (1) Since the signal propagation delay is varying and unknown, the relationship between the two adjacent target states is hard to describe; (2) limited by the underwater environment, it is more difficult to establish a target manoeuvring motion model; (3) the propagation speed of the underwater acoustic signal varies with the depth, and the propagation path will be curved instead of straight. Various parameters including signal propagation delay, target pitch angle and receiving frequency measured by the observer cannot be calculated as usual. In this paper, we improved a 3‐D constant turn (3D‐CT) model to match the underwater target motion. For the problems (1) and (3), this paper proposes a novel interacting multiple model underwater Gauss‐Helmert unscented Kalman filter (IMM‐UGHUKF) with isogradient sound velocity profile, which analytically describes the relationship between the state to be estimated and the passive measurement. This method augments the unknown signal emission time into the state with implicit equations, and transits the state by the Gauss–Helmert model. Simulation tests have been carried out, and the results show that IMM‐UGHUKF can significantly reduce the estimation error compared with other approaches.